1984
DOI: 10.1021/jm00375a021
|View full text |Cite
|
Sign up to set email alerts
|

Nonquaternary cholinesterase reactivators. 2. .alpha.-Heteroaromatic aldoximes and thiohydroximates as reactivators of ethyl methylphosphonyl-acetylcholinesterase in vitro

Abstract: We prepared six pairs of alpha-heteroaromatic aldoximes, RC(= NOH)H, and thiohydroximates, RC(= NOH)S-(CH2)2N(C2H5)2, where R represents various oxadiazole and thiadiazole rings. Each compound was characterized with respect to the following: structure, (hydroxyimino)methyl acid dissociation constant, nucleophilicity toward trigonal carbon and tetrahedral phosphorus, octanol-buffer partition coefficient, reversible inhibition of eel acetylcholinesterase (AChE), and in vitro reactivation of AChE inhibited by eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 1 publication
(1 reference statement)
2
14
0
Order By: Relevance
“…Treatment of alkylfurozans 569 with NBS in the presence of BPO or AIBN gives a-bromoalkyl derivatives 570 (Scheme 13.192) [477]. Similar results were obtained with 3-methylfuroxans 571 [478].…”
Section: Cycloaddition Reactions Of Benzofuroxanssupporting
confidence: 53%
See 1 more Smart Citation
“…Treatment of alkylfurozans 569 with NBS in the presence of BPO or AIBN gives a-bromoalkyl derivatives 570 (Scheme 13.192) [477]. Similar results were obtained with 3-methylfuroxans 571 [478].…”
Section: Cycloaddition Reactions Of Benzofuroxanssupporting
confidence: 53%
“…The halogen atom is readily displaced by a wide range of oxygen, sulfur, nitrogen, phosphorus, and carbon nucleophiles to give the corresponding products in good yields [477][478][479][480][481][482][483]. (577) shows strong antimicrobial activity [488].…”
Section: Cycloaddition Reactions Of Benzofuroxansmentioning
confidence: 99%
“…The structure of benzaldehyde O-[3-(5-tetrazolyl)propyl]oxime (73) and acetophenone O-[3-(5-tetrazolyl)propyl]oxime (74) was confirmed by the data from X-ray crystallographic analysis [62]. Unusual protonation is observed in the crystals of compound 74.…”
Section: Structurementioning
confidence: 82%
“…The 1 H NMR and 13 C NMR spectra of the oximes of triazole [9,14,23,[55][56][57], tetrazole [28,[58][59][60], 1,2,4-oxadiazole [32, 36], 1,2,5-oxadiazole [45,61], and 1,2,3-, 1,2,4- [62] and 1,2,5-thiadiazole [61,63] have been investigated in greatest detail. 645…”
Section: Structurementioning
confidence: 99%
“…Commercially available metronidazole (1) and 2-methyl-5-nitro imidazole (39) from Aldrich Chemical (Milwaukee, WI) were used. Compounds 2 [Calvino et al, 1980], 3, 31, 33 [Sorba et al, 1996], 4 [Boschi et al, 1997], 5 [Farrar, 1964], 12 [Kenley et al, 1984], 13-15 [Di Stilo et al, 1998], 17 [Rolando et al, 2003], and 34 [Kajfez et al, 1968] were synthesised according to the reported methods. The calculated log P (CLOGP) of the compounds was calculated using a CLOGP for Windows 4.0 software from the BioByte Corporation.…”
Section: Methodsmentioning
confidence: 99%